The Effect Of Work Environment, Work Discipline, Work Motivation, Compensation, And Work Load On Employee Performance At Cv Aneka Jaya Jember: English - Stevanus Rojer Alvando; Haifa; Hayatul Maspufah (Journal of Management, 2025)
This study aims to determine and analyze the influence of work environment , work discipline, work motivation, compensation and workload on employee performance at CV Aneka Jaya Rambipuji, Jember The research method used is quantitative. In this study, data was collected with observations, interviews, and questionnaires to 70 people, using saturated sample technique , for finding out the respondent’s perception about each variables. The analysis used includes data instrument tests (validity test and reliability test), multiple linear regression analysis, classical assumption test (normality test, multicollinearity test, heterokedasticity test), and hypothesis test (F test, t test, and determination coefficient test). The results of the t-test research in this study showed that the variables of work discipline and compensation had a positive and significant effect on employee performance while the work environment,motivation and work load had no a positive and significant effect on employee performance. Based on the result of the analysis, this study shows that the F test of the variables work environment , work discipline, work motivation, compensation and workload had a simultaneous effect on employee performance